The Way Batak People Decide Their Lives Preserving Their Old Customs Reshaped by Christianity - Tanjung, SM Parulian; Simbolon, Bintang R.; Jura, Demsy (Global Writing Academica Researching & Publishing, 2025)
Batak tribe is one of many tribes known in Indonesia. Batak tribe is only a small tribe in Indonesia, but they are popular with many strengths and achievements. One of the main uniqueness is up to now mostly of them still preserve their old customs and tradition of their ancestors, whenever and wherever they are. Although in early days long ago Batak tribe lived in the animism ways or any other old beliefs, by the grace of The Lord, Christian mission was successful in Batak land. Then the very old tradition slowly transformed adopting the Christian faith. Every generation of Batak inherit the tradition well through good education from their parents. They are proud of their tradition. And since the custom tradition they have is including all aspect of life, they plunge their lives in line with this tradition. This writing specifies the life of Batak subtribe, Toba, and mainly the Christian Batak. The research method applies the library research, qualitative method. Through analysis, the conclusion is how in general Batak people decide their lives, they just follow what their old customs tradition pattern, since the tradition has included all phases of life.